Glassy carbon electrodes deliver unpredictable reduction potentials for platinum(IV) antitumor prodrugs. (8th January 2016) - McCormick, Meghan C.; Schultz, Franklin A.; Baik, Mu-Hyun
Graphical abstract: The reduction of Pt(IV) complexes using glassy carbon (GC) electrode was found to be surprisingly erratic. More reproducible CVs are obtained with platinum metal electrodes and the unreliable and negatively shifted peak potentials are attributed to the oxide layer formed on the GC electrode. Abstract: Reductive activation of six-coordinate Pt(IV) complexes to afford square-planar Pt(II) complexes has exhibited surprisingly divergent and unpredictable cathodic peak potentials during cyclic voltammetry (CV) measurements under widely employed experimental conditions. A systematic, detailed investigation reveals that glassy carbon (GC) electrodes are responsible for this erratic behavior. More reproducible CVs are obtained with platinum metal electrodes, which display cathodic responses at much more positive potentials. The unreliable and negatively shifted peak potentials observed at GC are attributed to a non-uniform oxide layer that is formed on the electrode surface causing slow electron transfer. A simple procedure of repetitive scanning to reducing potentials is found to be effective for cleaning and activating the GC surface, such that it exhibits the more consistent and accurate peak potential responses seen with a Pt electrode.